Assessment of intra- and inter-regional interrelations between GABA+, Glx and BOLD during pain perception in the human brain – A combined 1H fMRS and fMRI study. (4th December 2017) - Cleve, Marianne; Gussew, Alexander; Wagner, Gerd; Bär, Karl-Jürgen; Reichenbach, Jürgen R.
Highlights: Combined functional 1 H MEGA-PRESS MRS and fMRI to explore interrelations between pain-evoked BOLD responses, GABA+ and Glx. No intra-regional association between left insular BOLD response and resting-state GABA+ and Glx or ΔGABA+ and ΔGlx changes. Negative association between BOLD in the SMA/MCC area and insular resting-state GABA+. Positive associations between insular ΔGlx and BOLD responses in multiple clusters of the pain network. Abstract: To explore brain activity and the related neurochemical processes, current research focuses increasingly on the combined acquisition of 1 H MR spectra and fMRI data to investigate potential associations between local metabolite resting state levels and stimulus-induced BOLD signal changes. In this study, whole-brain fMRI measurements and localized functional 1 H MEGA-PRESS MRS scans were conducted at 3T in healthy subjects prior to and during acute pain stimulation to quantify resting state GABA+/tCr and Glx/tCr levels in the insular cortex together with their stimulus-induced changes and to explore associations between these neurochemical parameters with intra-regional but also inter-regional BOLD responses. Inter-regionally, a significant negative correlation between the BOLD signal of a cluster in the supplementary motor area with overlap to the mid-cingulate cortex (R = −0.56, p = 0.004) and the insular resting state GABA+/tCr was obtained. Furthermore, pain induced insular ΔGlx was significantly positively associated with the BOLD signal in the left superior frontal gyrus, left and right inferior frontal gyrus, left inferior parietal lobe, left superior temporal gyrus, left anterior insula and right posterior insula, with R values ranging from 0.59 to 0.73 (p < 0.005). No intra-regional association was observed between BOLD and metabolite measures. These findings point toward interactions between metabolite levels and stimulus-induced BOLD responses in brain regions belonging to the pain processing network. The combination of fMRS and fMRI provides a powerful tool to improve our understanding about the complex system of neurochemical processes and brain activity within brain networks.